Perbandingan efektifitas pemberian imunisasi difteria satu kali, dua kali, dan tiga kali dengan penilaian titer antibodi pada anak - Nurhandayani dr; Hendri Wijaya; Inke Nadia Diniyanti Lubis; Ayodhia Pitaloka Pasaribu; Syahril Pasaribu; Chairuddin P. Lubis (Fakultas Kedokteran USU, 2013)
Abstract: Current issue diphtheria immunization, pertussis, tetanus (DPT) is whether there is a difference of immunity and effectiveness of administration once, twice, three times to establish immunity. There is some suggestion that antibodies against an antigen titer of low does not indicate susceptibility to the disease or reverse the amount of high titer nothing to do with immunity to a particular disease.Keywords: immunization; diphtheria; pertussis; tetanus; antibody titers